2010
DOI: 10.1152/ajpendo.00553.2009
|View full text |Cite
|
Sign up to set email alerts
|

LXRβ is the dominant LXR subtype in skeletal muscle regulating lipogenesis and cholesterol efflux

Abstract: Liver X receptors (LXRs) are important regulators of cholesterol, lipid, and glucose metabolism and have been extensively studied in liver, macrophages, and adipose tissue. However, their role in skeletal muscle is poorly studied and the functional role of each of the LXRalpha and LXRbeta subtypes in skeletal muscle is at present unknown. To study the importance of each of the receptor subtypes, myotube cultures derived from wild-type (WT) and LXRalpha and LXRbeta knockout (KO) mice were established. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 58 publications
3
21
1
Order By: Relevance
“…Our data obtained previously indicate also that in rat skeletal muscles LXRβ expression is higher than LXRα [27]. Others reported that LXRβ is the dominant isoform in the heart and skeletal muscle of mice [2,8,28] and in human skeletal muscle [29,30]. …”
Section: Disscusionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our data obtained previously indicate also that in rat skeletal muscles LXRβ expression is higher than LXRα [27]. Others reported that LXRβ is the dominant isoform in the heart and skeletal muscle of mice [2,8,28] and in human skeletal muscle [29,30]. …”
Section: Disscusionsupporting
confidence: 83%
“…Similar observation for murine heart was reported by Lei et al [8] where mRNA expression of both LXR isoforms was unchanged after GW3965 injections. Treatment with T0901317 did not affect the expression levels of LXRα and LXRβ also in the mouse myotubes [28,31]. It has been shown that LXRα expression is controlled by an autoregulatory mechanism and synthetic as well as natural LXR agonists increased LXRα expression in human macrophages, adipocytes, hepatocytes, skin fibroblasts and myotubes [30,32,33,34,35,36].…”
Section: Disscusionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human myotubes, chronic treatment with T0901317 increases cellular uptake of palmitate as well as cellular uncoupling in both control and T2D patients (76). In line with Muscat et al, we and others demonstrated that chronic LXR activation in vivo for 5 weeks reduced cholesterol content in mouse SM (1,77). We established that this reduction appeared in WT, LXRα KO, and LXRβ KO mice, indicating that both isoforms play a major role in RCT in SM.…”
Section: Lxr Function In Skeletal Musclesupporting
confidence: 87%
“…We have previously found that TO901317 decreases content of free cholesterol in rat skeletal muscles [33], however, not in the myocardium [11]. TO901317 also increased cholesterol efflux in mice myotubes [34,35], and according to Hessvik et al [35] LXRβ plays the dominant role in this process in skeletal muscle. Recently our group showed that LXRβ is more abundant than LXRα in the rat heart [11], and we speculate that decrease of free cholesterol level observed in the present study was caused mainly by LXRβ activation.…”
Section: Discussionmentioning
confidence: 93%